Peningkatan Rasio Penguatan Tegangan Keluaran Konverter DC-DC Sepic Dengan Modifikasi Kopel Induktor - Asnawanti Turnip; Dian Yayan Sukma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The purpose of this research is to design and simulate a DC-DC converter that can amplify the voltage generated by the 14 VDC voltage source to be inputted to an inverter without a transformer to produce a voltage of 220 VAC. The voltage generated by DC sources, both solar cells and storage batteries is generally relatively low to meet the voltage's minimum value to be used as the input voltage for the 220 V inverter. A modified SEPIC converter topology is used by adding a secondary winding to one converter inductor called a coupled inductor. The inductor coupling is used to increase the voltage proportional to the primary to the secondary winding ratio in the coupling inductor. This converter can produce a static voltage gain with a ratio of 17 times without increasing the duty-cycle value. The converter modeling circuit was built and simulated using MATLAB-SIMULINK 2016a software. The SEPIC DC-DC design converter with the modification of the inductor coupling can produce an average output voltage of 247 VDC. Keywords: SEPIC converter, inductor coupling, high gain ratio